Haplotypes from the SLC45A2 gene are associated with the presence of freckles and eye, hair and skin pigmentation in Brazil - Fracasso, Nádia Carolina de Aguiar; de Andrade, Edilene Santos; Wiezel, Cláudia Emília Vieira; Andrade, Claudia Caixeta Franco; Zanão, Lídia Renata; da Silva, Mateus Spinelli; Marano, Leonardo Arduino; Donadi, Eduardo Antônio; C. Castelli, Erick [UNESP]; Simões, Aguinaldo Luiz; Mendes-Junior, Celso Teixeira (My University, 2017)
The Solute Carrier Family 45, Member 2 (SLC45A2) gene encodes the Membrane-Associated Transporter Protein (MATP), which mediates melanin synthesis by tyrosinase trafficking and proton transportation to melanosomes. At least two SLC45A2 coding SNPs [E272K (rs26722) and L374F (rs16891982)] were reported influencing normal variation of human pigmentation. Here we aimed at evaluating the influence of haplotypes of 12 SNPs within SLC45A2 in the determination of eye, hair and skin pigmentation in a highly admixed population sample and comparing their frequencies with the ones found in data retrieved from the 1000 Genomes Project. To achieve this goal, 12 SLC45A2 SNPs were evaluated in 288 unrelated individuals from the Ribeirão Preto city area, Southeastern Brazil. SNPs were genotyped by PCR-RFLP or Allele-specific PCR, followed by polyacrylamide gel electrophoresis. Haplotypes of each individual were inferred by two independent computational methods, PHASE and Partition-Ligation–Expectation-Maximization (PL-EM) algorithms, and 34 different haplotypes were identified. The hp9 haplotype was the most frequent (58.3%) and was associated with the presence of blond/red hair, pale skin, blue eyes and freckles. All haplotypes significantly associated with dark or light pigmentation features harbor the 374L and 374F alleles, respectively. These results emphasize the role played by haplotypes at SLC45A2 in the determination of pigmentation aspects of human populations and reinforce the relevance of SNP L374F in human pigmentation.
Keywords: Brazil; Haplotypes; Pigmentation; SLC45A2; SNPs